The postcranial anatomy of Gorgonops torvus (Synapsida, Gorgonopsia) from the late Permian of South Africa - Bendel, Eva-Maria; Kammerer, Christian F.; Smith, Roger M. H.; Fröbisch, Jörg (PeerJ, 2023)
Gorgonopsians are among the most recognizable groups of synapsids from the Permian period and have an extensive but mostly cranial fossil record. By contrast, relatively little is known about their postcranial anatomy. Here, we describe a nearly complete, semi-articulated skeleton of a gorgonopsian (identified as Gorgonops torvus) from the late Permian Endothiodon Assemblage Zone of the South African Karoo Basin and discuss its paleobiological implications. Known gorgonopsian postcrania indicate morphological conservatism in the group, but the skeletal anatomy of Gorgonops does differ from that of other gorgonopsians in some respects, such as in the triangular radiale and short terminal phalanges in the manus, and a weakly developed distinction between pubis and ischium in ventral aspect of the pelvic girdle. Similarities between the specimen described herein and a historically problematic specimen originally referred to “Scymnognathus cf. whaitsi” confirm referral of the latter specimen to Gorgonops. Since descriptions of gorgonopsian postcrania are rare, new interpretations of the lifestyle and ecology of Gorgonopsia can be drawn from our contribution. We conclude that gorgonopsians were likely ambush predators, able to chase their prey over short distances and pin them down with strong forelimbs before using their canines for the kill. This is evidenced by their different fore- and hindlimb morphology; the former stouter and more robust in comparison to the longer, more gracile, back legs. Furthermore, the completeness of the study specimen facilitates calculation of an estimated body mass of approximately 98 kg, similar to that of a modern lioness.
Keywords: Synapsida; Therapsida; Gorgonopsia; Permian; Taxonomy; Gorgonops torvus; Postcranial anatomy